WEAGov Nigeria pilot study: Findings and policy implications - Ragasa, Catherine; Kyle, Jordan (International Food Policy Research Institute, 2023)
WEAGov assesses the state of women’s voice and agency in national agrifood policymaking. Like IFPRI’s Kaleidoscope Model, it adopts a policy process approach, looking at every stage of the policy cycle — from why certain issues become salient and how policy solutions to address them are designed, to the organizational strategies and budgetary outlays that shape policy implementation, to how policies are assessed against their objectives. Within each of these stages, WEAGov examines whether women are being considered, whether their voices are included, and whether they are influencing actions and decisions.